The Impact of the 'Planning Health in School' Programme on a Pair of Twins with Obesity - Margarida Vieira; Graça S. Carvalho (MDPI AG, 2022)
This case study describes the impact of the 'Planning Health in School' programme (PHS-pro) on the nutritional status and lifestyle behaviours of two twins with obesity. As part of a larger research project involving 449 adolescents in grade-6, PHS-pro aims at preventing obesity and guiding children towards healthy behaviours. Twins were evaluated for anthropometric measurements-height, weight, body mass index (BMI), waist circumference (WC), and lifestyle behaviours before (baseline) and after (8 months) PHS-pro and at a follow-up (one-year later). At the baseline, both twins were obese according to the international cut-off points of Cole. After PHS-pro, improvements in anthropometric parameters were found: the boy decreased his BMI by 10% and lost 9.0 cm in WC, while remaining obese; the girl decreased her BMI by 8% and lost 8.7 cm in WC, changing to the overweight category. At the follow-up, a slight increase in the anthropometric parameters was found in both twins; however, they did not return to the baseline values. The programme successfully promoted positive changes in behaviours and improved nutritional status, showing the long-term effects of the PHS-pro. Although it is a school-based intervention to prevent obesity, the PHS-pro is helpful in weight reduction even in children already with obesity.